Star formation rates and the kinematics of gas in the spiral arms of NGC 628. Issue 4 (June 2015) - Gusev, A. S.; Sakhibov, F.; Efremov, Yu. N.
Abstract The relations between star formation rates along the spiral arms and the velocities of gas inflow into the arms in the grand‐design galaxy NGC 628 were studied. We found that the radial distribution of the average star formation rate in individual star formation regions in regular spiral arms correlates with the velocity of gas inflow into the spiral arms. Both distributions have maxima at a galactocentric distance of 4.5–5 kpc. There are no correlations between the radial distributions of the average star formation rate in star formation regions in spiral arms and outside spiral arms in the main disc. We also did not find a correlation between the radial distribution of the average star formation rate in star formation regions in spiral arms and the H I column density. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)